Cigarette smoke induces mitochondrial DNA damage and activates cGAS-STING pathway: application to a biomarker for atherosclerosis. Issue 2 (24th January 2023) - Ueda, Keitaro; Sakai, Chiemi; Ishida, Takafumi; Morita, Kosuke; Kobayashi, Yusuke; Horikoshi, Yasunori; Baba, Akiko; Okazaki, Yuma; Yoshizumi, Masao; Tashiro, Satoshi; Ishida, Mari
Abstract: Cigarette smoking is a major risk factor for atherosclerosis. We previously reported that DNA damage was accumulated in atherosclerotic plaque, and was increased in human mononuclear cells by smoking. As vascular endothelial cells are known to modulate inflammation, we investigated the mechanism by which smoking activates innate immunity in endothelial cells focusing on DNA damage. Furthermore, we sought to characterize the plasma level of cell-free DNA (cfDNA), a result of mitochondrial and/or genomic DNA damage, as a biomarker for atherosclerosis. Cigarette smoke extract (CSE) increased DNA damage in the nucleus and mitochondria in human endothelial cells. Mitochondrial damage induced minority mitochondrial outer membrane permeabilization, which was insufficient for cell death but instead led to nuclear DNA damage. DNA fragments, derived from the nucleus and mitochondria, were accumulated in the cytosol, and caused a persistent increase in IL-6 mRNA expression via the cyclic GMP-AMP synthase (cGAS)-stimulator of interferon genes (STING) pathway. cfDNA, quantified with quantitative PCR in culture medium was increased by CSE. Consistent with in vitro results, plasma mitochondrial cfDNA (mt-cfDNA) and nuclear cfDNA (n-cfDNA) were increased in young healthy smokers compared with age-matched nonsmokers. Additionally, both mt-cfDNA and n-cfDNA were significantly increased in patients with atherosclerosis compared with the normal controls. Our multivariate analysis revealed that only mt-cfDNA predicted the risk of atherosclerosis. In conclusion, accumulated cytosolic DNA caused by cigarette smoke and the resultant activation of the cGAS-STING pathway may be a mechanism of atherosclerosis development. The plasma level of mt-cfDNA, possibly as a result of DNA damage, may be a useful biomarker for atherosclerosis.